UV–Vis Quantification of β-Carotene in Spinach under Raw and Boiled Conditions - Damanik, Sumayyah; Sartika Daulay, Anny; Ridwanto, Ridwanto; Harun, Fathur Rahman (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
β-Carotene is a provitamin A with strong antioxidant activity but is unstable to heat and oxidation. This study aimed to determine the β-carotene content of green spinach (Amaranthus viridis L.) and red spinach (Amaranthus tricolor L.) under fresh and boiled conditions using UV–Vis spectrophotometry. The assay was performed at 451 nm after maceration extraction with n-hexane:acetone:ethanol (2:1:1, v/v). Calibration in the range of 4–10 μg/mL showed excellent linearity (y = 0.064x – 0.003, r = 0.999). The results demonstrated that red spinach contained substantially higher β-carotene than green spinach. Boiling slightly increased the content in green spinach (17.16 → 18.76 ± 0.21 mg/g), while it caused a small decrease in red spinach (50.23 → 47.76 mg/g). These findings suggest that boiling has different effects depending on the spinach type, possibly due to a balance between heat-induced degradation and enhanced release from softened plant tissues. In conclusion, red spinach is a richer dietary source of β-carotene, but thermal processing reduces its stability. The validated UV–Vis spectrophotometric method is suitable for routine determination of β-carotene in leafy vegetables.